Treatment of Polycystic Ovary Syndrome in Adolescence - Vitek, Wendy; Hoeger, Kathleen M. (Seminars in Reproductive Medicine, 2014)
Adolescence is a time of rapidly changing reproductive hormones and menstrual patterns making diagnosis of polycystic ovary syndrome (PCOS) challenging in this population. Nonetheless, there is significant concern that the metabolic and reproductive abnormalities that emerge at adolescence associated with a diagnosis of PCOS have lifelong implications for the individual. There are limited data available on the best treatments for the adolescent with PCOS. The focus of treatment is often best served by attention to the individual abnormalities such as menstrual dysfunction, symptoms of androgen excess such as hirsutism and acne, possible metabolic dysfunction primarily seen with concurrent obesity, and concerns related to self-image and mood disorders.
Keywords: treatment; polycystic ovary syndrome; adolescence; obesity